(untitled) (Global Journal of Human-Social Science, 2013)
This article examines aesthetic components of print media news and feature stories and emphasizes on the need for present and upcoming journalists particularly in Nigeria to help protect the profession by always considering the aesthetic worth of their stories This is in view of the fact that with the growing importance of textual component of an average newspaper and magazine and continuous textual degeneration in most Nigerian newspapers and magazines not enough research works have been carried out in the area Of course investigations show that most of the research works on print media aesthetics in the country have been in the area of physical design and layout of newspaper and or magazine pages hence the article s emphasis that the aspect of news and feature contents needs commensurate concentration The article posits that as is the case in electronic media there are certain seemingly neglected inter-related variables that are by their nature considered as aesthetic fields in the written word news and features Accordingly the work identifies and illuminates certain aesthetic fields that should be recognized considered and applied by any journalist who irrespective of the structure or form of his writing aims at making reading a pleasurably rewarding exercise A position of this discourse is that a news or feature story that takes cognizance of the interrelated aesthetic fields is a bestseller to any newspaper or magazine outfit or reader